Spatial heterogeneity and environmental predictors of permafrost region soil organic carbon stocks - Mishra, Umakant; Hugelius, Gustaf; Shelef, Eitan; Yang, Yuanhe; Strauss, Jens; Lupachev, Alexey; Harden, Jennifer W.; Jastrow, Julie D.; Ping, Chien-Lu; Riley, William J.; Schuur, Edward A. G.; Matamala, Roser; et al. (Science Advances, 2021)
Large stocks of soil organic carbon (SOC) have accumulated in the Northern Hemisphere permafrost region, but their current amounts and future fate remain uncertain. By analyzing dataset combining >2700 soil profiles with environmental variables in a geospatial framework, we generated spatially explicit estimates of permafrost-region SOC stocks, quantified spatial heterogeneity, and identified key environmental predictors. We estimated that Pg C are stored in the top 3 m of permafrost region soils. The greatest uncertainties occurred in circumpolar toe-slope positions and in flat areas of the Tibetan region. We found that soil wetness index and elevation are the dominant topographic controllers and surface air temperature (circumpolar region) and precipitation (Tibetan region) are significant climatic controllers of SOC stocks. Our results provide first high-resolution geospatial assessment of permafrost region SOC stocks and their relationships with environmental factors, which are crucial for modeling the response of permafrost affected soils to changing climate.